INVITRO INVESTIGATION OF ANTIBACTERIAL, ANTIOXIDANT ACTIVITY AND PHYTOCHEMICAL SCREENING OF STEAM DISTILLED FRUIT EXTRACT OF TERMINALIA CHEBULA - C.SOUMYA; C.SOUMYA; H.A.PRUTHVI AVADHANI; R.VIDHYA; VINUTHA MOSES (International Journal of Pharma and Bio Sciences, 2015)
Nature has provided mankind with several plants which contain natural substances which cure diseases & promote health. Considering its medicinal property, extraction of oil from plant fruit materials of Terminalia chebula was used, as it proved to preserve the original qualities of the plant and also causes no degradation of the materials used. Steam Distillation process was used for the extraction of oil at lab scale using the available resources. The present study investigated, the phytochemical screening of T chebula extract, it revealed the presence of terpenoids, alkaloids,volatile acids and tannins .The antibacterial potential of fruit extract evaluated against clinical isolates showed the exhibition of antibacterial effect against all isolates. The antioxidant activity tested, showed a maximum inhibition in the range of 75-90% of 1mg/ml of extract and their IC50 value was found to be 620 µg/ml. The high content of total phenolic compound (440 µg GAE / mg of extract) revealed the antioxidant activity of the extract.